Quantification of Faropenem in Human Plasma by High-performance Liquid Chromatography - Nirogi, Ramakrishna V. S.; Kandikere, Vishwottam N.; Wishu, Shrivastava; Mudigonda, Koteshwara (Arzneimittelforschung, 2005)
A simple, sensitive and specific high-per-formance liquid chromatography (HPLC) method with ultraviolet detection (315 nm) was developed and validated for quantitation of faropenem (CAS 106560-14-9), the newest addition to the group of ß-lactam antimicrobials, in human plasma. Following solid-phase extraction using Waters OasisTM SPE cartridges, the analyte and internal standard (hydrochlorothiazide, CAS 58-93-5) were separated using an isocratic mobile phase of 10 mmol/L acetate buffer (pH adjusted to 7.0 with dilute acetic acid) / methanol / triethyl amine (70/30/0.03, v/v/v) on reverse phase Waters symmetry ® C18 column. The lower limit of quantitation was 200 ng/mL, with a relative standard deviation of less than 2 %. A linear range of 200 to 25000 ng/mL was established. This HPLC method was validated with between-batch and within-batch precision of 1.6 to 2.3 % and 0.4 to 1.6 %, respectively. The between-batch and within-batch bias was − 3.1 to 5.3 % and − 6.0 to 1.5 %, respectively. Frequently coadministered drugs did not interfere with the described methodology. The stability of faropenem in plasma was excellent, with no evidence of degradation during sample processing (autosampler) and 30 days storage in a freezer. This validated method is sensitive, simple and repeatable enough to be used in pharmacokine-tic studies.
Keywords: Antimicrobial drugs, ß-lactam; CAS 106560-14-9; Faropenem, HPLC quantification in human plasma